Gender Equality Paradise Revisited: The Dynamics of Gender Disbalance in Russian Engineering from the Late Soviet Time to the 2010s. Issue 1 (2nd January 2022) - Rudenko, Nikolay; Antoshchuk, Irina; Maliushkin, Roman; Zemnukhova, Liliia
Abstract : The Soviet Union, during the late socialist period, is believed to have achieved impressive progress in making gender equality in STEM come true. The collapse of the Soviet Union and rapid transition to the market economy, accompanied by destruction of industrial production and economic decline, brought unprecedented challenges to the engineering profession. How has the post-socialist transition affected gender (dis)balance? We use rich, unique, and previously unexplored big data from a Russian-speaking social network, VKontakte, to answer this question. Our primary finding is that there have been negative gender dynamics since the late Soviet times, the gender gap has widened, and gender inequality in engineering has become more acute. Women's presence in the profession has considerably decreased. Gender segregation, both vertical and horizontal, in higher education and at the workplace has solidified. We found minor gender discrepancies in job mobility patterns, and even slightly declining mobility since Soviet time. However, changing mobility patterns does not seem to have affected the gender imbalance positively. We find partial support for the leaky pipeline argument in higher engineering education and paid employment. We conclude that the 1990s was a period of harsh masculinization and intensifying gender inequality in engineering in Russia, and the current situation is still under the influence of these trends.